EDUCATIONAL MARKETING INFORMATION SYSTEMS AT ISLAMIC EDUCATIONAL INSTITUTIONS - Tio Ari Laksono; Sulistyorini Sulistyorini (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: Educational Marketing Information Systems at Islamic Educational InstitutionsDelays in presenting educational marketing information will cause information not to reach customers quickly and accurately. Marketing educational services is a strategy to improve the quality of education which is the most important element for the quality and progress of the level of education in an educational institution. Marketing is done so that the public knows the advantages and programs owned by the madrasa. Customer satisfaction with educational institutions is identical to customer satisfaction regarding the services provided. This type of research is library research with a qualitative approach. The research process is descriptive analysis, namely by collecting data, compiling, clarifying, and analyzing. Marketing activities can be carried out with various channels or several media, with the hope that there will be three stages of change, namely: changes in knowledge, changes in attitudes, and changes in desired actions. Educational institutions must be able to create community-oriented educational service programs that adapt to the needs of madrasas. Educational institutions must strive to create a positive image in the eyes of the community so that people can make decisions for their sons and daughters to choose the madrasa. Abstrak: Sistem Informasi Pemasaran Pendidikan pada Lembaga Pendidikan IslamKeterlambatan dalam menyajikan informasi pemasaran pendidikan akan menyebabkan informasi tidak sampai kepada pelanggan dengan cepat dan tepat. Pemasaran jasa pendidikan merupakan strategi peningkatan mutu pendidikan yang merupakan elemen terpenting bagi kualitas serta kemajuan taraf pendidikan pada suatu lembaga pendidikan. Pemasaran dilakukan agar masyarakat mengetahui keunggulan dan program-program yang dimiliki oleh madrasah. Kepuasan pelanggan terhadap lembaga pendidikan identik dengan kepuasan pelanggan mengenai pelayanan yang diberikan. jenis penelitian ini adalah penelitian kepustakaan (library research) dengan pendekatan kualitatif. Pada proses penelitiannya bersifat analisis deskriptif, yaitu dengan cara mengumpulkan data, menyusun, mengklarifikasikan, dan menganalisis. Kegiatan pemasaran dapat dilakukan dengan berbagai saluran atau sejumlah media, dengan harapan terjadinya tiga tahapan perubahan, yaitu: perubahan pengetahuan, perubahan sikap dan perubahan tindakan yang dikehendaki. lembaga pendidikan harus dapat membuat program-program layanan pendidikan yang berorientasi kepada masyarakat yang menyesuaikan dengan kebutuhan madrasah. Lembaga pendidikan harus berusaha untuk menciptakan citra yang positif dimata masyarakat sehingga masyarakat dapat membuat keputusan untuk putra dan putrinya agar memilih madrasah tersebut.